Palgrave advances in modern military history - Hughes, Matthew, d 1965-; Philpott, William James (Palgrave Macmillian, 2006)
This collection constitutes the definitive guide for advanced undergraduate and postgraduate students studying modern military history. It provides the reader with a clear and up-to-date survey of the significant debates, interpretations and historiographical shifts for a series of key themes in military history, ranging from the fifteenth to the twenty-first centuries, and across the technological, political, social, and cultural dimensions of military history